Policy Analysis Of Regional School Operational Assistance In Madrasahs In Malang District - Irkhami, Adib Azhar; Wahidmurni, Wahidmurni; Ghofur, Abdul (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
The government of Kabupaten Malang, in its commitment to help unravel the problems of education financing at the local level, issued the BOSDA policy through Perbup No. 19/2020. This research aims to analyze BOSDA policies starting from planning, implementation, and evaluation. This research uses a qualitative approach with a phenomenological type of research through interviews with parties involved in the preparation process and implementing the BOSDA policy, in this case, the Legal Section of the Regional Secretariat, BAPPEDA, the Pendma Section of the Ministry of Religious Affairs and interviews with L.P Ma'arif and DPRD as representatives of policy constituents. Other data sources were obtained through observation and document studies related to BOSDA. The results showed that in the realm of policy formulation, BOSDA has been prepared by the applicable mechanism. Furthermore, the allocation of BOSDA funds to Madrasahs in 2021 and 2022 was constrained by the lack of regional income due to post-pandemic budget refocusing. Furthermore, in 2023 the BOSDA policy was changed to the Scholarship Program without going through a legal review process and analysis of the resulting output.  In the realm of implementing the BOSDA policy in Madrasahs, the Pendma Section of the Ministry of Religious Affairs of Malang Regency as the BOSDA implementer has been carried out well by its authority and resources. With the change of BOSDA policy to scholarships, the authority of Pendma Kemenag was replaced by Bakesbangpol. The results of the administrative evaluation show that the change of BOSDA into a scholarship program leaves no authority to monitor the accuracy of the use of scholarship funds that have been given. Then the results of the judicial evaluation, the BOSDA policy that turned into a scholarship was not preceded by an in-depth study in the legal realm and the impact of policy success through the resulting output. Furthermore, the results of the political evaluation showed a lack of positive acceptance from the constituents of the policy recipients, seen from the perceived impact of the policy and the efforts of Madrasah residents in continuing to demand that the BOSDA policy be carried out by the initial mechanism.